What do young people want? - Information requirements on clinical research. (24th May 2012) - Newman, J; Van't Hoff, W; Callens, C; Tibbins, C; Davies, H
Abstract : Aims: To study young peoples' views on current National Research Ethics Service (NRES) guidance on information sheets and consent forms for researchers and reviewers Methods: A series of workshops where developed and held at routine meetings of the NIHR Medicines for Children Research Network (MCRN) Young Person's Advisory Group, commencing in September 2011. The first set of activities focused on the main purpose of the patient information leaflet, what did young people want to know before participating in a trial, what information is/is not important what format should be used and what are young people's views on the standard layout of information prescribed by NRES. Responses were collated, summarised and grouped. Results: In total 81 young people provided input into the first set of activities. 100% of young people stressed the importance of producing age appropriate patient information leaflets that highlighted key facts about what the research is, why is it being done and what patients need to do (e.g. have an injection) in order to agree to participate in a study. Young people broke down the information into two main categories; general information (e.g information about the research, why is it being done and what patients need to do) and more importantly the safety aspects of the trial (e.g. are there likely to be any serious side effects). Although there was no general consensus as to the order of headings there was 100% consensus on the information young people didn't want, which is normally found in part two of information leaflets and information required for obtaining informed consent, not necessarily for obtaining assent. Conclusion: This is a large study of young peoples' views on the information they need to consider to participate in research and comes at a time of increasing number of studies in children. The multiplicity and diversity of responses suggests there is no single ideal model of information but key principles emerge. This collaboration with NRES will allow incorporation of young people's views into their guidance, improving the information that children receive and thereby improving their ability to make informed choices on participation.